Research Assessment Reform, Non-Traditional Research Outputs, and Digital Repositories: An Analysis of the Declaration on Research Assessment (DORA) Signatories in the United Kingdom - Hurrell, Christie (Evidence Based Library and Information Practice, 2023)
Objective – The goal of this study was to better understand to what extent digital repositories at academic libraries are active in promoting the collection of non-traditional research outputs. To achieve this goal, the researcher examined the digital repositories of universities in the United Kingdom who are signatories of the Declaration on Research Assessment (DORA), which recommends broadening the range of research outputs included in assessment exercises.Methods – The researcher developed a list of 77 universities in the UK who are signatories to DORA and have institutional repositories. Using this list, the researcher consulted the public websites of these institutions using a structured protocol and collected data to 1) characterize the types of outputs collected by research repositories at DORA-signatory institutions and their ability to provide measures of potential impact, and 2) assess whether university library websites promote repositories as a venue for hosting non-traditional research outputs. Finally, the researcher surveyed repository managers to understand the nature of their involvement with supporting the aims of DORA on their campuses.Results – The analysis found that almost all (96%) of the 77 repositories reviewed contained a variety of non-traditional research outputs, although the proportion of these outputs was small compared to traditional outputs. Of these 77 repositories, 82% featured usage metrics of some kind. Most (67%) of the same repositories, however, were not minting persistent identifiers for items. Of the universities in this sample, 53% also maintained a standalone data repository. Of these data repositories, 90% featured persistent identifiers, and all of them featured metrics of some kind. In a review of university library websites promoting the use of repositories, 47% of websites mentioned non-traditional research outputs. In response to survey questions, repository managers reported that the library and the unit responsible for the repository were involved in implementing DORA, and managers perceived it to be influential on their campus.Conclusion – Repositories in this sample are relatively well positioned to support the collection and promotion of non-traditional research outputs. However, despite this positioning, and repository managers’ belief that realizing the goals of DORA is important, most libraries in this sample do not appear to be actively collecting non-traditional outputs, although they are active in other areas to promote research assessment reform.